Golgi Apparatus fragmentation in dilated cardiomyopathy and its relationship with the alteration of vesicular transport. (3rd October 2022) - Gimenez-Escamilla, I; Perez-Carrillo, L; Portoles, M; Martinez-Dolz, L; Tarazon, E; Rosello-Lleti, E
Abstract: Background: The Golgi Apparatus (GA) is an important membrane-bound organelle implied in many physiological events, as trafficking, processing and sorting of newly membrane and secretory proteins and lipids. Nevertheless, these functions can be dysregulated in a diversity of pathologies due to the alteration of the GA morphology, such as cardiovascular diseases. Previously, we described in dilated cardiomyopathy (DCM) alterations in shape and size of the secretion vesicles of GA that was related to a worse functional situation. The patients had smaller, more ellipsoidal and more numerous vesicles with a higher content of natriuretic peptides (1). This situation can be related with Golgi fragmentation, a status characterized by the presence of a dispersed GA both in physiological and pathophysiological conditions (2). However, a greater understanding of Golgi fragmentation in DCM is necessary. Purpose: We attempted to analyse the components of the vesicular Golgi transport and the Golgi fragmentation in cardiac tissue samples from DCM patients, paying special attention to GM130, as one of the main molecules related with the Golgi fragmentation. Methods: We analysed vesicular Golgi transport genes in human hearts by RNA-sequencing in 13 samples from DCM patients and 10 control hearts (CNT), and the miRNAs that regulate their expression by ncRNA sequencing (DCM, n=20; and CNT, n=8). Finally, we investigated changes in the protein levels of GM130 and its phosphorylated state (pGM130) by western blot with 22 DCM and 6 CNT samples in total. Results: We found 134 differentially expressed genes related to the GA, and 15 of them were involved in the secretion of Golgi vesicles. Among these molecules, VAMP4, a v-SNARE related with the Golgi fragmentation, is found to be downregulated (−1.27-Fold; P<0.05). Moreover, we have observed a downregulation in the expression of GOLGA2, the gene that encodes GM130 (−1.24; P<0.05). Furthermore, its regulator, hsa-miR-17-5p (−1.42; P<0.01) was also downregulated. In this sense, we have found no changes in GM130 protein levels between DCM patients and CNT group. In contrast, pGM130, molecule that it has been used as a biomarker of Golgi fragmentation, was overexpressed in DCM patients (1.19; P<0.05). Conclusion: We found a deregulation of genes related to the vesicle secretion in the GA, which together with the changes in vesicular morphology previously observed, suggests an alteration in the rate of secretion in response to the needs of the DCM patients. In addition, the increase in the phosphorylated protein GM130 suggests the presence of fragmentation in DCM patients that could be related to the alteration in vesicular transport. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos III European Regional Development Fund (ERDF)